Capacity building of 'Aisyiyah Makassar City Branch Leaders through citizen journalism training - Yahya, Muhammad; Arni, Arni; Syukri, Syukri; Sabriani, Sabriani; Mudiyawati, Andita; Lutfiah, Andi Qonita (Community Empowerment, 2025)
One form of modern journalism is citizen journalism, where non-professional individuals can play an active role in the information production process. 'Aisyiyah, as a religious organization active in women's empowerment, encourages its members to contribute to citizen journalism to disseminate progressive Islamic values. The purpose of this community service (PkM) is to enhance the skills of 'Aisyiyah cadres in writing news and captions for news portals and social media. The method used in this service is an audience-centered method, consisting of four stages: partner needs identification, training, mentoring, and evaluation. The training covers basic journalism materials, including journalistic introduction, journalistic ethics, laws and regulations, coverage techniques, information gathering, news writing (5W+1H), photography, and videography using mobile phone cameras. The results of the activity indicate that the participants' understanding of basic journalism increased by 75%, but some participants still require further mentoring.